2002
DOI: 10.1289/ehp.02110301
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane potential: a novel biomarker of oxidative environmental stress.

Abstract: ArticlesEpidemiologic analyses, traditionally based on long-term cohort or case-control studies, provide retrospective causal associations between exposure to a particular environmental stressor and an exposure-related disease end point. Recent research initiatives have propelled a shift toward exploring molecular epidemiology and molecular biological markers (biomarkers) as a means of providing more immediate, quantitative risk assessment of potentially deleterious environmental exposures. We compared, in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…To further assess the effect of pyocyanin on mitochondria, we measured mitochondrial membrane potential. Alteration in mitochondrial membrane potential has been shown to be a sensitive indicator of oxidant damage (53). Using a fluorescent probe-based assay, we observed that exposure of cells to pyocyanin resulted in a decrease in mitochondrial membrane potential (Fig.…”
Section: Subcellular Localization Of Pyocyanin Redox Cyclingmentioning
confidence: 91%
See 1 more Smart Citation
“…To further assess the effect of pyocyanin on mitochondria, we measured mitochondrial membrane potential. Alteration in mitochondrial membrane potential has been shown to be a sensitive indicator of oxidant damage (53). Using a fluorescent probe-based assay, we observed that exposure of cells to pyocyanin resulted in a decrease in mitochondrial membrane potential (Fig.…”
Section: Subcellular Localization Of Pyocyanin Redox Cyclingmentioning
confidence: 91%
“…Mitochondrial membrane potential was measured fluorometrically by previously described methods (7,53). Briefly, the cells were grown in 96-well plates and incubated with or without pyocyanin for 24 h. The medium was removed, and the wells were rinsed twice with HBSS.…”
Section: Methodsmentioning
confidence: 99%
“…A decreased Δψ m is indicative of defective oxidative phosphorylation and a lower capacity of generating ATP, 48 and is used as a marker of cellular and mitochondrial viability. 49 It is however worthwhile to note that, to counteract oxidative stress, the mitochondria and the cytoplasm are equipped with detoxifying enzymes and non-enzymatic antioxidants. 50 Therefore, although oxidants are constantly being generated by the mitochondria, the antioxidant defense system is capable of detoxifying them, preventing damage to cytoplasmic components.…”
Section: Ama Increases Mitochondrial Omentioning
confidence: 99%
“…The gradient drives the synthesis of adenosinetriphosphate (ATP). DC m is a marker of the state of energization of the organelle [12][13][14][15][16][17][18][19][20][21], and can be influenced by the energetic status of the cell depending not strictly on mitochondrial activity alone but also on oxygen consumption, cytosolic ATP production and NADH:NAD 1 (nicotinamide adenine dinucleotide) ratio [12,22]. Bioenergetics is of importance in infectious disease because immune reactions are important consumers of energy [23].…”
Section: Mitochondrial Membrane Potential (Dc M ) As a Marker Of Mitomentioning
confidence: 99%